2023
DOI: 10.1071/wr22159
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting bait uptake by the grey squirrel (Sciurus carolinensis) and the future delivery of oral contraceptives

Abstract: Context. Invasive species negatively affect natural communities and human activities. The grey squirrel is an invasive species in the UK, causing damage to forestry and the decline of the native red squirrel. Oral contraceptives have the potential to reduce numbers of grey squirrels; however, to be effective a sufficient proportion of a population must consume a bait containing contraceptives. Aims. The objective of this study was to estimate the efficacy of delivering baits via feeders to grey squirrels and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…As more oral contraceptives become available for wildlife applications, understanding factors that affect patterns of individual and population bait uptake is essential to maximise consumption of these agents by the target species. The study by Beatham et al (2024), featured in this Special Issue, showed that season, feeder density and grey squirrel density are important factors affecting bait uptake, with more squirrels consuming bait from three feeders per hectare than from one per hectare, and with a higher proportion of animals feeding on bait in summer than in winter.…”
Section: Wildlife Fertility Control: What Has Happened Since 2008?mentioning
confidence: 93%
“…As more oral contraceptives become available for wildlife applications, understanding factors that affect patterns of individual and population bait uptake is essential to maximise consumption of these agents by the target species. The study by Beatham et al (2024), featured in this Special Issue, showed that season, feeder density and grey squirrel density are important factors affecting bait uptake, with more squirrels consuming bait from three feeders per hectare than from one per hectare, and with a higher proportion of animals feeding on bait in summer than in winter.…”
Section: Wildlife Fertility Control: What Has Happened Since 2008?mentioning
confidence: 93%